Does supportive legislation guarantee access to pregnancy termination and postabortion care services? Findings from a facility census in Central Province, Zambia. Issue 4 (3rd September 2018) - Cresswell, Jenny A; Owolabi, Onikepe O; Chelwa, Nachela; Dennis, Mardieh L; Gabrysch, Sabine; Vwalika, Bellington; Mbizvo, Mike; Filippi, Veronique; Campbell, Oona M R
Abstract : Introduction: Zambia is one of the few countries in Africa to permit termination of pregnancy (TOP) on a wide range of grounds. However, substantial barriers remain to TOP and postabortion care (PAC). Methods: We conducted a census of 153 facilities between March and May 2016. We defined facilities according to whether they met basic and/or comprehensive signal functions criteria for TOP and PAC. We linked our facility data to census data to estimate geographic accessibility under different policy scenarios. Results: Overall, 16% of facilities reported they had performed a TOP and 39% performed a PAC in the last year. Facilities were twice as likely to use medical methods for TOP compared with surgical methods, and four times more likely for PAC. Considerably more facilities had performed TOP or PAC than met the basic or comprehensive signal functions criteria, indicating services were being performed in facilities below essential quality standards. Under current Zambian law for non-emergency scenarios, 21% of women in Central Province lived within 15 km of a facility with basic capability to provide TOP; if midlevel providers were trained to provide TOP, this would increase to 36%. Conclusion: A supportive legislative framework is essential, but not in itself sufficient, for adequate access to services. Training midlevel providers, in line with WHO guidance, and ensuring equipment is available in primary care can increase accessibility of TOP and PAC. While both medical and surgical methods need to be available, medical abortion is a safe and effective method that can be provided in low-resource settings.